2007
DOI: 10.1128/iai.01156-06
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus granulosus Antigen B Impairs Human Dendritic Cell Differentiation and Polarizes Immature Dendritic Cell Maturation towards a Th2 Cell Response

Abstract: Despite inducing a strong host cellular and humoral immune response, the helminth Echinococcus granulosus is a highly successful parasite that develops, progresses, and ultimately causes chronic disease. Although surgery remains the preferred therapeutic option, pharmacological research now envisages antihelminthic strategies. To understand the mechanisms that E. granulosus uses to escape host immunosurveillance and promote chronic infection, we investigated how two hydatid cyst components, purified antigen B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
135
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(152 citation statements)
references
References 64 publications
10
135
1
5
Order By: Relevance
“…AgB significantly inhibits polymorphonuclear cell recruitment (Rigano et al, 2001;Shepherd et al, 1991), modulates dendritic cell differentiation and polarizes immature DC maturation towards a Th2 cell response (Rigano et al, 2007). After establishment in the host, the hydatid cyst produces a large amount of AgB , which can alter the Th1/Th2 ratio from a predominant Th1 response in the early stage of infection to a Th2 response (Rigano et al, 2001), indicating that AgB is a modulator of the T cell response benefiting parasite survival.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…AgB significantly inhibits polymorphonuclear cell recruitment (Rigano et al, 2001;Shepherd et al, 1991), modulates dendritic cell differentiation and polarizes immature DC maturation towards a Th2 cell response (Rigano et al, 2007). After establishment in the host, the hydatid cyst produces a large amount of AgB , which can alter the Th1/Th2 ratio from a predominant Th1 response in the early stage of infection to a Th2 response (Rigano et al, 2001), indicating that AgB is a modulator of the T cell response benefiting parasite survival.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…It has a molecular size of circa 8 kDa on sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) (Lightowlers et al, 1989;Shepherd and McManus, 1987) under reduced conditions. The function of AgB in the parasite's biology is not completely elucidated, but several studies have shown that the molecule may be involved in the modulation of the host immune response; for instance, as a protease inhibitor that inhibits neutrophil chemotaxis (Shepherd et al, 1991;Virginio et al, 2007), promoting a non-protective Th2 response by interfering with monocyte differentiation, and by modulating DC maturation (Kanan and Chain, 2006;Rigano et al, 2007). One study has suggested that AgB could be involved in the processes of lipid uptake or detoxification (Chemale et al, 2005).…”
Section: E Granulosus Antigen Bmentioning
confidence: 99%
See 2 more Smart Citations
“…A feature shared by many helminths is their capacity to suppress TLR-mediated DC activation by microbial PAMP. Numerous studies have reported the inhibitory effects of helminth-derived components on TLR-induced activation as determined by pro-inflammatory cytokine production and expression of MHC class II/costimulatory molecules [28,[33][34][35][36][37][38][39]. The pathways underlying this suppression are, however, still poorly understood.…”
mentioning
confidence: 99%